KONTRIBUSI PARTISIPASI MASYARAKAT PESISIR, PEMANFAATAN SUMBER DAYA LOKAL, KESADARAN LINGKUNGAN DAN KEARIFAN LOKAL DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN KOTA BATAM - Yuanita FD Sidabutar; Nur Effendi Anwar; Malahayati Rusli Bintang (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Sustainable development in coastal areas requires active participation from all stakeholders, particularly local communities who directly interact with the environment. This study aims to examine the contribution of coastal communities to the sustainable development of Batam City from the perspective of regional planning. Using a descriptive qualitative approach, data were collected through field observations, in-depth interviews, and document analysis. The findings indicate that community participation in Batam’s coastal areas remains partial and has yet to be fully integrated into regional planning processes. Nevertheless, there are notable local initiatives focused on environmental conservation and the development of marine-based sustainable livelihoods. Key supporting factors include local wisdom, environmental awareness, and collaboration between communities and local governments. The study recommends strengthening community capacity, improving access to planning information, and implementing participatory policies that engage coastal residents from planning to implementation. These findings are expected to serve as a basis for formulating inclusive and sustainable coastal development strategies in Batam City.